Sistem Penjadawalan Satpam Menggunakan Algoritma Genetika dan Seleksi Tournament - Ilham Firman Ashari; Ardi Gaya Manalu; Rahmat Setiawan; Mugi Praseptiawan; Dita Alviuni P; Sisilia Juli A (Politeknik Negeri Batam, 2021)
Institut Teknologi Sumatera (ITERA) is one of the new state universities on the island of Sumatra. ITERA has developed and has a large area and many buildings, of course it requires a lot of security guards to maintain security and order in the campus environment. The working hours of security guards at ITERA are from morning to night. ITERA is required to make a watch or shift schedule for security guards, where currently the scheduling is still done manually and has not been systemized automatically. Genetic Algorithm can be used in the scheduling process automatically and optimally by going through several stages. The result of the research is that the automatic scheduling system was successfully built, from the security data used as many as 16 data obtained scheduling from Monday to Sunday along with its working hours.